SIMBOL MODERASI BERAGAMA DALAM EKOSISTEM PLURALISME DI KAMPUNG REHOBOT INDRAMAYU - Yohanes Irmawandi; Nur Hidayat, Mufti (Parahyangan Catholic University, 2023)
This research explores the symbols of religious moderation in the daily practices of the community in Rehobot Village, Indramayu, West Java, as a response to the complexity of the pluralistic ecosystem in Indonesia. The main focus is on conflicts between religious communities caused by negative prejudices and violations of Freedom of Religion and Belief. In response, the government has initiated the Moderation of Religion program, aiming to foster an inclusive attitude and uphold human rights amidst religious diversity. The research employs a qualitative approach, utilizing observation, in-depth interviews, and literature review techniques to uncover symbols of religious moderation in Rehobot Village. The findings indicate that everyday practices, such as non-segregated public burials, cross-faith sports activities, and mutual support in religious celebrations, serve as symbols of religious moderation deeply rooted in Rehobot's cultural fabric. Furthermore, the Village Bhinneka policy and the roles of religious leaders as unifiers and promoters of tolerance strengthen religious moderation at the local level. These practices reflect the commitment of the Rehobot community to harmoniously coexist amidst diverse beliefs, creating an inclusive environment that can serve as an example for other communities in fostering tolerance and interfaith dialogue. This research provides profound insights into how symbols of religious moderation can serve as crucial pillars in supporting the pluralistic ecosystem in Indonesia.